A Comparative Study to Evaluate the Diagnostic Accuracy of Bedside Hydrogen Peroxide Test and Light’s Criteria in Differentiating Pleural Effusions as Transudate and Exudate - Rao, Trishna; B P, Preethi (RGUHS journal of medical sciences, 2025)
Background Pleural effusions are common manifestations of a variety of pathologies. The specific cause must be identified to initiate timely treatment. The primary step in establishing a diagnosis is to differentiate transudative and exudative effusions for which Lightrsquos criteria have been accepted as the gold standard. However recent studies investigating Lightrsquos criteria have revealed high sensitivity for exudates but low specificity. This prompted us to evaluate bedside hydrogen peroxide H2 O2 test as an alternative to Lightrsquos criteria.Methods A cross-sectional study involving 100 subjects was conducted to determine the diagnostic accuracy of the bedside H2nbspO2nbsptest in differentiating transudative and exudative pleural fluids using the Lightrsquos criteria as the reference standard. According to Lightrsquos criteria a pleural effusion is classified as an exudate when the pleural fluid proteinserum protein ratio gt0.5 or the pleural fluid lactate dehydrogenase LDHserum LDH gt0.6. A transudate is diagnosed when these criteria are not met. In the H2nbspO2nbsptest an exudate is identified by the appearance of profuse bubbling within one minute of adding H2nbspO2nbspto the pleural fluid whereas the absence of bubbling indicates a transudate.nbspResults A male preponderance was observed with a higher incidence of pleural effusion among urban dwellers. Among the study population 74 were chronic tobacco consumers and 62 were chronic alcoholics. The H2nbspO2nbsptest demonstrated a sensitivity of 88.52 specificity of 94.87 positive predictive value of 96.4 negative predictive value of 88.4 and an overall diagnostic accuracy of 91.0.Conclusion The simple bedside H2nbspO2nbsptest facilitates rapid categorization of pleural fluid as transudate or exudate thereby reducing diagnostic turn around time and allowing for earlier initiation of treatment. Additionally the H2 O2 test is cost-effective making it more viable option in resource-deficient laboratory settings. nbsp